The effect of using blended learning strategy on science achievement among fourth grade students in Tafila Governorate Basira Education Directorate - Alzidaneen, Huda Abdalsalam (Journal of Educational and Psychological Sciences, 2021)
This study aimed to find out the effect of the blended learning strategy on the achievement of the fourth-grade students in the basic science subject in the Basira Basira Directorate of Education in Tafila Governorate. The study members were selected by intentional method, and they numbered (52) students from fourth grade students in Al-Harith Basic School for Boys, and the two divisions were randomly assigned and distributed into two divisions. One of them is a control group, which was (27) students who were taught the traditional strategy, and the other is (25) students as an experimental one who learned the blended learning strategy. Its validity and reliability were verified and then applied to the study sample.The results of the study showed a statistically significant difference in the achievement of the study sample at the level of significance )α≤0.05) between the averages of the scores of the two study groups in favor of the experimental group that learned with the blended learning strategy. Achieving science among fourth-grade students in Tafila Governorate by securing the necessary infrastructure to facilitate the application of blended learning by equipping laboratories and ensuring the validity of the Internet.
Keywords: blended learning; science education and fourth grade; science education